Lexical Item Learning Via Multimedia Annotations. - Leong, Dr Lai Mei (2008)
The ubiquitous computers with multimedia technology serve as an attractive learning tool because they are able to deliver integrated, different source media as well as access these media easily and instantaneously. Thus, to take advantage of these qualities to help language learners, multimedia annotations of lexical items, which present information of the items via printed text, audio mode, still pictures and animation, are utilized. This paper reports on the effects of integrating multimedia annotations in expository texts on the learning of lexical items by 109 Science students from Universiti Sains Malaysia. In this within-subjects design study, the participants read expository texts on the computer.